2007
DOI: 10.1021/ja072904r
|View full text |Cite
|
Sign up to set email alerts
|

Label Transfer Chemistry for the Characterization of Protein−Protein Interactions

Abstract: A new label transfer method is presented that overcomes most of the limitations of current systems. A protein of interest is tagged with tetra-cysteine sequence (FlAsH Receptor Peptide (FRP)) that binds tightly and specifically to a chimeric molecule 3,4-dihydroxyphenylalanine-biotin-4′,5′-bis (1,3,2-dithioarsolan-2-yl)fluorescein (DOPA-biotin-FlAsH). Upon brief periodate oxidation, the DOPA moiety is cross-linked to nearby surface-exposed nucleophiles. Boiling the products in excess dithiol dissolves the FlAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 18 publications
0
40
0
1
Order By: Relevance
“…␣-Rpn1 and ␣-Rpn2 were produced in mouse. The DOPA-biotin-FlAsH chimera (DBF) cross-linking reagent (19) and the DOPA-Gal4 AD peptide have been described (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…␣-Rpn1 and ␣-Rpn2 were produced in mouse. The DOPA-biotin-FlAsH chimera (DBF) cross-linking reagent (19) and the DOPA-Gal4 AD peptide have been described (20).…”
Section: Methodsmentioning
confidence: 99%
“…The proteins indicated in the figure were added to the reaction mix at the same time as peptide addition. Cross-linking to detect mono-Ub/ proteasome interaction was done as described (19) with the following changes. 110 nM 26 S or 19 S proteasome was mixed with 10 M CCPGCC-Ub in TR reaction buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both fragmentation spectra were identical, it can be concluded that this species is the intermolecular crosslinked peptide. Figure 3 presents MALDI-MS/MS annotated spectra of intramolecular crosslinked P1c, P2c, and P3c (for noScheme 3 menclature see Liu et al [38]). These peptides can be seen as branched cyclic peptides because the DSSpeptide bond is also an amide bond.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly pressing problem in biology is the study of protein interactions. A previously introduced approach based on the tetracysteine tag ( Figure 3a) uses a trifunctional compound containing a biarsenical dye to bind to the protein of interest, a crosslinker triggered by addition of sodium periodate to induce tethering to binding partners, and biotin for detection of the interaction partner after SDS-PAGE and western blotting [52]. This affinity labeling method has recently been applied to study the interaction between ubiquitin and the proteasome [53].…”
mentioning
confidence: 99%